Do Digital Innovation and Risk Disclosure Control Performance? Evidence from Banking in ASEAN-6 - Tjondro, Elisa; Cintya, Margaretha Oerip; Seto, Silvia; Suherman, Yemima Gracia (Jurnal Ilmiah Akuntansi, 2021)
The aim of this study to explain the influence of digital innovation and risk disclosure on bank performance in ASEAN countries. The research sample was 70 banks in ASEAN from Indonesia, Malaysia, Thailand, Philippines, Singapore, and Vietnam in the 2015-2018 period in which the annual reports used dual language or English. The study used regression panel analysis. Digital innovation and risk disclosure used content analysis. Indicators of digital innovation used digital branches and mobile banking.Â Â The results of the study found that the higher the digital innovation, the greater the bank profitability. However, only mobile banking has a significant effect. The next finding is the disclosure of potential risks in the annual report gave a negative signal to ASEAN banking, resulting in lower bank profitability. The uniqueness of the ASEAN setting is dominated by a very large, dynamic, and rapidly adapting population of productive age to digital technology.